DEKADENSI PERAN RAWI HADIS PEREMPUAN DARI MASA KE MASA (Pendekatan Historis) - Hasan Mahfudh (IAIN Kediri, 2021)
This paper discusses in depth the role of Muslimah in receiving and spreading hadith. According to the historical trajectory of hadith, the role of women in accessing, studying and disseminating it had been up and down. From the quantitative aspect, in contrast to the phenomenon of male narrators which is increasingly widespread, the average number of female narrators tends to decrease and decrease. The declining in the role of women in narrating hadith did not just happen. By tracing the historicity of the development of Muslims from time to time, various factors are found influencing this decadence. The increasing role of women in the domestic sphere from time to time has also reduced their chances of transmitting hadith. Positively, this phenomenon can confirm that the process of transmitting hadith is a historical event and not an artificial one as some orientalists think.